EFFORTS TO IMPROVE STUDENTS’ LONG JUMP ABILITY THROUGH RESISTANCE ROPE MEDIA AT GRADE V OF SDN 17 MANDAU - Berliana Barutu (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The background of this research was the students’ low ability in performing long jump squat style. Thus, the researchers tried to take action in order to increase students' ability. The effort was using resistance rope learning media. This research was a classroom action research conducted on 23 students in class VB. The implementation of this research was in the odd semester of the 2019–2020 school year. The research instrument was the student's long jump ability observation sheet. The results of the research in the first cycle obtained classical completeness as many as 17 students or 73.91% and increased to 86.95% with the number of students who completed as many as 20 people. Based on the results of the study, it was concluded that the students’ ability to perform the long jump squat style increased through the use of resistance rope media.